Accountability during Performance Appraisals: The Development and Validation of the Rater Accountability Scale. Issue 1 (1st January 2023) - Tenbrink, Andrew P.; Speer, Andrew B.
ABSTRACT: The purpose of the current study was to create and validate a new measure of rater accountability (RA) for use in performance appraisal (PA) contexts. Previous research has identified the accountability audience as an important moderator of the effects of RA that existing measures do not consider. This new measure of RA, the Rater Accountability Scale (RAS), was developed to capture accountability pressures from different audiences. Across two studies that sampled current managers, the RAS scores achieved adequate fit and acceptable reliability. Initial construct-related validity evidence was collected by exploring relationships with convergent measures, rater characteristics, and appraisal outcomes. Overall, these findings provide support for the use of the RAS in research and applied settings while also helping to build the nomological network of RA.